A comprehensive overview of exosome lncRNAs: Emerging biomarkers and potential therapeutics in gynecological cancers - Wang, Min; Fu, Lulu; Xu, Ying; Ma, Shuai; Zhang, Xueying; Zheng, Lianwen (Frontiers in Oncology, 2023)
Ovarian, endometrial, and cervical cancer are common gynecologic malignancies, and their incidence is increasing year after year, with a younger patient population at risk. An exosome is a tiny “teacup-like” blister that can be secreted by most cells, is highly concentrated and easily enriched in body fluids, and contains a large number of lncRNAs carrying some biological and genetic information that can be stable for a long time and is not affected by ribonuclease catalytic activity. As a cell communication tool, exosome lncRNA has the advantages of high efficiency and high targeting. Changes in serum exosome lncRNA expression in cancer patients can accurately reflect the malignant biological behavior of cancer cells. Exosome lncRNA has been shown in studies to have broad application prospects in cancer diagnosis, monitoring cancer recurrence or progression, cancer treatment, and prognosis. The purpose of this paper is to provide a reference for clinical research on the pathogenesis, diagnosis, and treatment of gynecologic malignant tumors by reviewing the role of exosome lncRNA in gynecologic cancers and related molecular mechanisms.